1997
DOI: 10.1210/endo.138.4.5063
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 and 9-cis-Retinoic Acid Act Synergistically to Inhibit the Growth of LNCaP Prostate Cells and Cause Accumulation of Cells in G1*

Abstract: Recent studies have suggested that the active metabolite of vitamin D3, 1,25-dihydroxyvitamin D3, can inhibit the growth and/or induce the differentiation of a variety of cell types and that these characteristics might be useful in the treatment of some cancers. Retinoids also promote the differentiation and inhibit the growth of some cells. That the vitamin D receptor acts as a heterodimer with the retinoid X receptor (RXR) suggests that there may be functional interactions between 1,25-dihydroxyvitamin D3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(101 citation statements)
references
References 21 publications
5
95
1
Order By: Relevance
“…The data found associating vitamin D derivatives and retinoids are in accordance with the results obtained by many authors, who described a synergistic effect exerted by 1,25(OH) 2 D 3 or its analogues and retinoids on different cell lines (35-37). Blutt et al (38) reported the synergistic inhibition in the growth of LNCaP prostate cancer cells exerted by the combination of 1,25(OH) 2 D 3 or EB 1089 and 9-cis retinoic acid, and Zugmayer et al (39) showed that EB 1089, if added alone to human pancreatic adenocarcinoma cells, did not significantly inhibit growth, while, in combination with all-trans retinoic acid caused a growth-inhibitory effect of 90%. We also demonstrated the synergistic effect exerted by the combination of 1,25(OH) 2 D 3 or its analogues (KH 1060 and EB 1089) and 9-cis retinoic acid on SH-SY5Y human neuroblastoma cell proliferation, whereas the combination with all-trans retinoic acid led to a quite different behaviour (32).…”
Section: Resultsmentioning
confidence: 99%
“…The data found associating vitamin D derivatives and retinoids are in accordance with the results obtained by many authors, who described a synergistic effect exerted by 1,25(OH) 2 D 3 or its analogues and retinoids on different cell lines (35-37). Blutt et al (38) reported the synergistic inhibition in the growth of LNCaP prostate cancer cells exerted by the combination of 1,25(OH) 2 D 3 or EB 1089 and 9-cis retinoic acid, and Zugmayer et al (39) showed that EB 1089, if added alone to human pancreatic adenocarcinoma cells, did not significantly inhibit growth, while, in combination with all-trans retinoic acid caused a growth-inhibitory effect of 90%. We also demonstrated the synergistic effect exerted by the combination of 1,25(OH) 2 D 3 or its analogues (KH 1060 and EB 1089) and 9-cis retinoic acid on SH-SY5Y human neuroblastoma cell proliferation, whereas the combination with all-trans retinoic acid led to a quite different behaviour (32).…”
Section: Resultsmentioning
confidence: 99%
“…Our present data, however, strongly support a direct action of IL-1b on the control of LNCaP cell proliferation through activation of the sphingomyelin cascade. 1,25 (OH 2 )-D 3 , which triggers sphingomyelin hydrolysis in di erent cellular systems (Okazaki et al, 1989(Okazaki et al, , 1990, exerts potent antiproliferative and di erentiating activity in LNCaP cells grown in the presence of serum (Skowronski et al, 1993), determining cell cycle arrest in G 1 (Blutt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These VDR/RXR heterodimers function as transcription factors in regulating vitamin D-mediated gene expression (Liao et al, 1990;Kliewer et al, 1992;MacDonald et al, 1993). Several reports have shown that 9-cis-RA and 1,25-VD act synergistically to inhibit the growth of prostate cancer cells via the VDR/RXR heterodimer (Blutt et al, 1997;Zhao et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Even though these cells express similar levels of functional VDRs, they respond to 1,25-VD-mediated inhibitory effects differently. For example, LNCaP, an androgen-dependent prostate cancer cell line, is significantly inhibited by 1,25-VD; however, the PC-3, DU 145, and ALVA-31 cell lines are less sensitive to the antiproliferative action mediated by 1,25-VD (Miller et al, 1992;Schwartz et al, 1994;Miller et al, 1995;Blutt et al, 1997). These results suggest that VDR expression is not solely responsible for the growth suppression induced by 1,25-VD (Skowronski et al, 1993;Zhuang et al, 1997;Zhuang and Burnstein, 1998).…”
Section: Introductionmentioning
confidence: 99%